Prices and market power in mental health care: Evidence from a major policy change in the Netherlands. (27th January 2021) - Brouns, Chiara; Douven, Rudy; Kemp, Ron
Abstract: In the Dutch health care system of managed competition, insurers and mental health providers negotiate on prices for mental health services. Contract prices are capped by a regulator who sets a maximum price for each mental health service. In 2013, the majority of the contract prices equaled these maximum prices. We study price setting after a major policy change in 2014. In 2014, mental health care providers had to negotiate prices with each individual health insurer separately, instead of with all insurers collectively as in 2013. Moreover, after a cost‐price revision, the regulator increased in 2014 maximum prices by about 10%. Insurers and mental health providers reacted to this policy change by setting most contract prices below the new maximum prices. We find that in 2014 mental health providers with more market power, that is, a higher willingness‐to‐pay measure, contracted significantly higher prices. Some insurers negotiated significantly lower prices than other insurers but these differences are unrelated to an insurers' market share.